HUBUNGAN ANTARAAKTIVITAS FISIK DENGAN KADAR GULA DARAH PADA LANJUT USIA WANITA DI KOMUNITAS DAHLIA SENJA LIMO, DEPOK. - Srihani Wulandari, (2023)
Background : Physical activity can affect blood sugar levels by improving insulin sensitivity and speeding up the process of reducing blood sugar, regular and moderate intensity physical activity can help keep blood sugar levels stable, but there are several factors such as the type of physical activity, duration, and conditions Individual health can also affect how physical activity affects blood sugar levels. The aim of this research was to determine the relationship between physical activity and blood sugar levels in the elderly in the elderly community. Design : The design of this study used a cross-sectional method based on the results of measuring physical activity using the International Physical Activity Questionnaire (IPAQ) questionnaire for measuring blood sugar levels using a glucometer. The sample in this study were the elderly in the Dahlia Senja Limo Depok Elderly Community, totaling 40 samples. In this study using univariate test and bivariate test using SPSS 25. Results : The results obtained from 40 respondents, there are (45.0%) elderly who have moderate physical activity and there are (95.0%) elderly who have normal blood sugar levels. The value of p = 0.000 with p <0.05. There is no relationship between physical activity and blood sugar levels in the elderly in the Dahlia Senja, Limo Depok.